INTEGRATING DUOLINGO AND QUIZIZZ IN ENGLISH LANGUAGE LEARNING FOR CIVIL ENGINEERING STUDENTS: A LITERATURE REVIEW - Juvrianto Chrissunday Jakob; Sylvia Irene Persulessy; Reynold Pieter Jordan Vigeleyn Nikijuluw; Phuong Le-Hong; Nihla Afdaliah (Epigram, 2026)
English proficiency is an essential skill for civil engineering students, as it supports their ability to access technical information, understand engineering literature, and communicate ideas in academic and professional contexts. However, many students still face challenges in developing adequate English language skills due to limited motivation and conventional learning approaches. The integration of digital technology has emerged as a promising solution to enhance language learning in higher education. This study aims to examine the potential use of Duolingo and Quizizz in supporting English language learning for civil engineering students. The study employs a literature review method by analyzing previous studies related to technology-assisted language learning. The results indicate that Duolingo contributes to vocabulary acquisition and grammar development through gamified learning activities, while Quizizz enhances student engagement and supports formative assessment through interactive quizzes. The findings suggest that integrating mobile learning applications into English language learning can create more engaging and flexible learning environments. Therefore, technology-based learning tools have the potential to improve English language competence among civil engineering students and support more effective language learning practices in higher education.